Long-course preoperative chemoradiation versus 5 × 5 Gy and consolidation chemotherapy for clinical T4 and fixed clinical T3 rectal cancer: long-term results of the randomized Polish II study. (13th June 2019) - Ciseł, B; Pietrzak, L; Michalski, W; Wyrwicz, L; Rutkowski, A; Kosakowska, E; Cencelewicz, A; Spałek, M; Polkowski, W; Jankiewicz, M; Styliński, R; Bębenek, M; et al.
Abstract: Background: This trial evaluated whether preoperative short-course radiotherapy and consolidation chemotherapy (CCT) were superior to chemoradiation in rectal cancers with clinical (c)T4 or fixed cT3. Previously, we reported early results showing no differences in the radical surgery rate (primary end point). In the short-course/CCT group, we observed lower acute toxicity of preoperative treatment and better overall survival (OS). We updated results to determine whether the benefit in OS was sustained and to evaluate late complications. Patients and methods: Patients with cT4 or fixed cT3 rectal cancer were randomized either to preoperative 5 × 5 Gy and three cycles of FOLFOX4 or to chemoradiation (50.4 Gy with bolus 5-Fu, leucovorin and oxaliplatin). Results: Patients ( N = 515) were eligible for analysis, 261 in the short-course/CCT group and 254 in the chemoradiation group. The median follow-up was 7.0 years. The difference in OS was insignificant [hazard ratio (HR) 0.90; 95% confidence interval (CI) 0.70–1.15; P = 0.38). However, the difference in early OS favouring short-course/CCT previously reported was observed again, being 9% at 3 years (95% CI 0.5% to 17%). This difference disappeared later; at 8 years OS was 49% in both groups. There was no difference in disease-free survival (HR 0.95; 95% CI 0.75–1.19; P = 0.65) at 8 years 43% versus 41% in the short-course/CCT group versus the chemoradiation group, respectively. The corresponding values for cumulative incidences of local failure and distant metastases did not differ and were HR = 1.08, 95% CI 0.70–1.23, P = 0.60, 35% versus 32% and HR = 1.10, 95% CI 0.68–1.23, P = 0.54, 36% versus 34%, respectively. The rate of late complications was similar ( P = 0.66), grade 3+ being 11% versus 9% in the short-course/CCT group versus the chemoradiation group, respectively. Conclusion: The superiority of preoperative short-course/CCT over chemoradiation was not demonstrated. Clinical trial number: The trial is registered as ClinicalTrials.gov number NCT00833131.